Advancing water security in Africa with new high-resolution discharge data - Akpoti, Komlavi; Velpuri, Naga Manohar; Mizukami, N.; Kagone, S.; Leh, Mansoor; Mekonnen, Kirubel; Owusu, Afua; Tinonetsana, Primrose; Phiri, Michael; Madushanka, Lahiru; Perera, Tharindu; Paranamana, Thilina Prabhath; et al. (2024)
VegDischarge v1, which covers over 64,000 river segments in Africa, is a natural river discharge dataset produced by coupled modeling; the agro-hydrologic VegET model and the mizuRoute routing model for the period 2001-2021. Using remote sensing data and hydrological modeling system, the 1-km runoff field simulated by VegET, was routed with mizuRoute. Performance metrics show strong model reliability, with R² of 0.5–0.9, NSE of 0.6–0.9, and KGE of 0.5–0.8 at the continental scale. The total average annual discharge for Africa is quantified at 3271.4 km³·year−1, with contributions to oceanic basins: 1000.0 km³·year−1 to the North Atlantic, primarily from the Senegal, Gambia, Volta, and Niger Rivers; 1327.2 km³·year−1 to the South Atlantic, largely from the Congo River; 214.7 km³·year−1 to the Mediterranean Sea, predominantly from the Nile River; and 729.4 km³·year−1 to the Indian Ocean, with inputs from rivers such as the Zambezi. The dataset is valuable for stakeholders and researchers to understand water availability, its temporal and spatial variations that affect water-related infrastructure planning, sustainable resource allocation, and the development of climate resilience strategies.